Biosorption Performance of Biochar from Exhausted Kahwa Coffee on Cadmium Removal Under Various Operational Parameters - Nika Rahma Yanti; Aninda Tifani Puari; Frisca Lora Amalya; Rusnam Rusnam; Rahmi Awalina (The University of Lampung, 2025)
The primary goal of this study was to investigate the biosorption performance of biochar derived from exhausted kahwa coffee (EKC) on removing heavy metal ion, Cd²⁺ in the solution. The operational parameters, for instance pH, dosage and contact time, were varied in a certain range and the efficiency and the capacity of removal were determined. The pH was in a range of 5 – 11, while the biochar dosage in a range of 0.075 – 0.15 g and the contact time was in between 30 – 180 minutes. The batch biosorption test showed that the EKC biochar had higher removal performance in alkaline condition, with a proposed pH of 10. Meanwhile, the applied dosage showed that addition of 0.1 g EKC biochar was more effective than adding more dosage. Furthermore, the batch experiments showed that 60 minutes of biosorption process resulted in more effective removal compared to the longer biosorption time. According to the ANOVA analysis on the three conditions, it was shown that the pH and contact time had significant effects on the removal performance of EKC biochar on cadmium ion in the solution. Keywords: Biochar, biosorption, Exhausted kahwa coffee, Heavy metal ion, Operational parameters.